Gender inequality in islamic religious education - Fauziah, Syifa; Kartika Dewi, Nufitriani (Early Publishing, 2025)
This study investigates gender inequality in Islamic education, focusing on access, participation, and the overall benefits for both genders. The primary objective is to analyze the root causes of gender disparity and its broader impacts on social and economic development. Utilizing a qualitative research design with a descriptive-analytical approach, data were collected through literature review, interviews with stakeholders, and observations of Islamic educational institutions. The findings reveal that cultural norms, socioeconomic factors, and policy gaps significantly contribute to the disparity, limiting women's opportunities in education and beyond. The results underscore the psychological and economic consequences of this inequality, hindering societal progress. This research concludes by offering actionable strategies, including inclusive policies, curriculum reform, and enhanced community awareness, to foster gender equality. The study highlights the necessity of collaborative efforts among governments, educational institutions, and communities to create a fair and inclusive educational environment, empowering individuals regardless of gender.